Recurrent CEP85L–PDGFRB fusion in patient with t(5;6) and imatinib-responsive myeloproliferative neoplasm with eosinophilia. Issue 7 (July 2013) - Winkelmann, Nils; Hidalgo-Curtis, Claire; Waghorn, Katherine; Score, Joannah; Dickinson, Helen; Jack, Andrew; Ali, Sahra; Cross, Nicholas C. P.
Abstract: Fusion genes involving the catalytic domain of tyrosine kinases (TKs) play an important role in the pathogenesis of hematological malignancies and solid tumors. In BCR–ABL1 -negative myeloproliferative neoplasms (MPNs) several different tyrosine kinase fusion events have been described, most commonly involving the genes encoding the platelet-derived growth factor receptor alpha ( PDGFRA ) or beta ( PDGFRB ). Since the introduction of small molecule kinase inhibitors, TK fusions have emerged as prime therapeutic targets. Here, we report a recurrent CEP85L–PDGFRB fusion in a patient with eosinophilia and an MPN. The fusion was confirmed by specific amplification of the genomic breakpoints and reverse transcription polymerase chain reaction (PCR). The patient was treated with imatinib and achieved hematologic and cytogenetic remission. Minimal residual disease screening over 3 years with nested PCR failed to detect CEP85L–PDGFRB mRNA or genomic DNA, confirming a long-term molecular remission on imatinib.